The museum as architectural representation - Cortegana, Rodolfo (2023)
The importance of architecture as a cultural manifestation in society has been for the museum one of its most important tools. The history of architecture has read and amplified from its architectural representation the formal symbolism that museum buildings possess, in our country the boom generated from the neoliberal currents from the Peruvian State at the end of the 20th century and the beginning of XXI, placed buildings that were not exempt from such valuations. Since the birth of the republic, architectural ideas brought from Europe in the 19th century have been installed and placed in our museums, thus generating an epidermal appropriation that would serve as a tool for valuation, adopting the imaginary of archaeologists in most the cases.